2021
DOI: 10.7759/cureus.20013
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Pre-pandemic Measures of Religiosity and Psychological Responses to the COVID-19 Pandemic: A Secondary Analysis of Data From a Multi-Country Study

Abstract: Background The uncertainty and socioeconomic disruption caused by the COVID-19 pandemic have been frequently associated with negative affective responses, particularly depression and anxiety. People from countries across the globe have frequently resorted to religious coping to deal with these emotions. However, there are conflicting results in the literature about the impact of prior patterns of religious belief and practice on emotional responses to COVID-19. Methods In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…One of the best-known coping strategies to deal with the negative effects that the COVID-19 pandemic had on the mental health of the population was having religious beliefs, attitudes, or practices (90)(91)(92)(93)(94). Nevertheless, our study participants who believed in a religion showed a higher score for fear of COVID-19, in line with other studies (95)(96)(97). According to Krok et al ( 98), the fear of COVID-19 also intensified the effect of religiosity on meaning-making, leading individuals to seek religious activities for emotional support and coping strategies.…”
Section: Main Findingssupporting
confidence: 88%
“…One of the best-known coping strategies to deal with the negative effects that the COVID-19 pandemic had on the mental health of the population was having religious beliefs, attitudes, or practices (90)(91)(92)(93)(94). Nevertheless, our study participants who believed in a religion showed a higher score for fear of COVID-19, in line with other studies (95)(96)(97). According to Krok et al ( 98), the fear of COVID-19 also intensified the effect of religiosity on meaning-making, leading individuals to seek religious activities for emotional support and coping strategies.…”
Section: Main Findingssupporting
confidence: 88%